2021
DOI: 10.1364/boe.440939
|View full text |Cite
|
Sign up to set email alerts
|

Detection of carbamazepine in saliva based on surface-enhanced Raman spectroscopy

Abstract: Carbamazepine (CBZ) is a commonly used drug for the treatment of epilepsy. Due to the narrow effective range, CBZ concentration was usually monitored with blood draw from patients. Frequent blood draw is inconvenient and causes physical and psychological pain. Therefore, highly-sensitive, rapid, label-free, and non-invasive drug detection methods can be alternatives to bring a relief. In this work, we have proposed a method for the non-invasive detection of CBZ using surface-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 12 publications
(9 citation statements)
references
References 53 publications
1
5
0
Order By: Relevance
“…The limit of detection (LOD) was calculated using a signal-to-noise ratio (S/N) of 3: the specific LOD values were 0.01 µg•mL −1 for CBZ, 1 µg•mL −1 for CBZE, and 1 µg•mL −1 for CBZD (Figure S4). Though the LOD value of CBZ was about ten times higher than other literature has demonstrated, in which CBZ in salvia can be achieved by SERS [28]. The LODs in our study met the actual clinical testing requirements.…”
Section: Detection Of Simulated Samplessupporting
confidence: 53%
See 1 more Smart Citation
“…The limit of detection (LOD) was calculated using a signal-to-noise ratio (S/N) of 3: the specific LOD values were 0.01 µg•mL −1 for CBZ, 1 µg•mL −1 for CBZE, and 1 µg•mL −1 for CBZD (Figure S4). Though the LOD value of CBZ was about ten times higher than other literature has demonstrated, in which CBZ in salvia can be achieved by SERS [28]. The LODs in our study met the actual clinical testing requirements.…”
Section: Detection Of Simulated Samplessupporting
confidence: 53%
“…Molecules 2023, 28,128 could not be focused well, and the droplet edge was easily boiled by the laser (Fi resulting in a very large signal-to-noise ratio on the SERS spectrum. Moreover, s purity signals were present.…”
Section: Surface Treatment Optimization Of Silicon Wafermentioning
confidence: 99%
“…Subsequently, it was continuously stirred and heated to 60 °C. When it boils, 6 ml of 1 wt% sodium citrate solution and 2.5 ml of 0.1 M silver nitrate solution 33 were added (Fig. 2b).…”
Section: Synthesis Of Aunps and Au@ag Npsmentioning
confidence: 99%
“…In the case of drugs that require long-term use or are effective only in a narrow concentration range, the first crucial improvement achieved was the development of an approach that departed from the invasive procedure of blood collection in favour of performing tests using the patient's urine or saliva [69]. An important example here is the monitoring of the concentration of carbamazepine (CBZ), a commonly used anti-epilepsy drug.…”
Section: Drugs Monitoringmentioning
confidence: 99%
“…The idea was to monitor the concentration of this drug in saliva using a gold-silver core-shell nanomaterial. Cheng et al showed that it is possible to monitor this drug in a concentration range of from 3.26 × 10 −9 M for CBZ in saliva [69] (see Figure 9). Barveen, Wang, and Chang proposed a different non-invasive approach to drug detection, that of detecting chlorpromazine (CPZ) in human saliva or urine [70].…”
Section: Drugs Monitoringmentioning
confidence: 99%